Artificial Intelligence in Tennis. A Social Perspective - Marian-Petre PRĂJESCU; Beatrice Aurelia ABALAȘEI (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae)
Introduction: Artificial Intelligence (AI) is increasingly influencing professional sports, including tennis, by supporting technical analysis, training optimization, and decision-making processes. Understanding how different groups perceive AI in the sports context is essential for its effective integration. Objective: The study aims to explore and compare the social representations of artificial intelligence in tennis among athletes and non-athletes. Methods: The research employed the word association technique (Vergès, 2001) and the social representation indicator (Havârneanu, 2001). The sample included 60 participants, divided equally into two groups: 30 athletes and 30 non-athletes. The analysis focused on the frequency and order of appearance of words associated with AI in a sports context. Results: Distinct differences emerged between the two groups. Athletes primarily associated AI with advanced technology that enhances performance and efficiency, while aspects such as injury prevention or ethical concerns were less prominent. Non-athletes emphasized “equipment and infrastructure,” reflecting a more concrete and device-oriented perception of AI in sports. Conclusions: The study highlights divergent perceptions of AI between athletes and non-athletes, which may influence how AI-based technologies are accepted and implemented in tennis. Understanding these differences is crucial for tailoring AI applications to meet the expectations and needs of various stakeholders in sports.